Falling Use of Cash and Demand for Retail Central Bank Digital Currency - Khiaonarong, Tanai (IMF Working Papers; Working Paper ;, 2022)
Cash use in most countries is falling slowly. On the margin, younger adults favor cash substitutes over cash. For older adults it is the reverse. Revealed preference tied to a changing population age structure seems to be the main influence on the demand for cash and why it is falling. Cash use may continue to fall, and card use (the main cash substitute) may fall by more, if CBDC is issued. The extent of this reduction depends on the demand for retail CBDC and the incentives (primarily transaction fees) that can play a determining role in CBDC adoption and use.